Economic Losses due to Subclinical Mastitis in Dairy Animals: A Study in Bidar District of Karnataka - Rathod, Prakashkumar; V., Shivamurty; Desai , Anant Rao (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
A total of 421 pooled milk samples from zebu/desi cows, crossbred cows and buffaloes were screened to study the incidence rate and economic losses due to subclinical mastitis (SCM) in 10 villages of two blocks under the World Bank funded, Karnataka watershed Development Department sponsored - Sujala III project during last two years. Nine out of 421 samples (2.13%) were found positive for SCM by CMT. The economic losses due to subclinical form of mastitis were estimated in the range of INR 21,677/- to INR 88,340/- pre animal for a lactation period. The study found that incidence of SCM was also related to managemental practices followed by dairy farmers.
Keywords: Mastitis; Sub-clinical mastitis; Economic loss; management practices; Bidar; Sujala project